Decolonizing Patriarchal Readings: Badriyah Fayumi’s Feminist Interpretation of the Biased Verses on Domestic and Sexual Violence in the Qur’an - Ifa, Afifatul; Akbar, Akbar (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2025)
Violence against women remains an escalating phenomenon and a critical issue in contemporary social development. The Qur’an presents numerous verses that directly and indirectly addresses matters of violence, gender relations, and the protection of women. However, many classical exegetical traditions remain influenced by patriarchal constructs, often producing interpretations that are misaligned with principles of justice and gender equity. This article analyzes the feminist Qur’anic hermeneutics of Badriyah Fayumi concerning verses related to violence against women, particularly QS al-Nisā’ [4]:19, QS al-Nisā’ [4]:34, and QS al-Isrā’ [17]:32. Employing a qualitative-descriptive approach grounded in library research and content analysis, the study examines Fayumi’s major work, Tubuh, Seksualitas, dan Kedaulatan Perempuan. The findings reveal that Fayumi develops a contextual-feminist interpretive framework centered on Maqāṣid al-Syarīʿah, substantive justice, and women lived experiences. Her exegesis rejects the legitimacy of domestic violence, expands the conceptual boundaries of sexual misconduct, and affirms women’s autonomy as moral agents. Fayumi’s contributions offer a significant foundation for constructing a humanistic and progressive Qur’anic interpretation that aligns with gender equality and ethical integrity. This study argues that feminist tafsīr is not a counter-narrative to religion, but rather a revitalization of the Qur’an’s ethical message aimed at fostering a more just society free from gender-based violence.